PEMANFAATAN LIMBAH MINYAK GORENG MENJADI LILIN JELANTAH (The Utilization Of fried Oil Waste Into Used Cooking Candle) - Ergantara, Rani Ismiarti; Nasoetioen, Panisean; Sulastri, Sulastri; Atmono, Atmono; Maurinnisa, Dhea Aulia; Lestari, Agustia Indah (Program Studi Manajemen Fakultas Ekonomi dan Manajemen Universitas Malahayati, 2023)
Used cooking oil is one type of hazardous waste produced from the food processing process with cooking oil. This waste can come from households, stalls, restaurants and other food businesses. Repeated use of cooking oil will result in oil damage because unsaturated fats oxidize to form peroxide compounds and cause many diseases and cause environmental pollution. This activity aims to provide education about the importance of a healthy and clean environment, know how to use used cooking oil waste, and help reduce environmental pollution to be clean and healthy. The methods used are the planning stage, the collection stage of tools and materials, the process stage of making used cooking candles, and the socialization stage. The result of this activity is the use of used edible oil waste into used cooking candle can be an innovative solution in an effort to reduce the level of environmental pollution.